Exploring Challenges Towards Learning Mathematics Among Secondary School Students in Nepal - Pokhrel, Maheshwor (Academic Journal of Mathematics Education, 2023)
Mathematicians had been concerned with everyday problems. However, today’s students are uninterested in learning mathematics. The main objective of this research is to identify students’ challenges to learning mathematics. Employing an interpretative research paradigm, the study utilizes a narrative research design involving eight students from public and private schools in the Kaski district. To achieve the research objective, in-depth interviews were conducted with research participants. I had narrated views about challenges towards learning mathematics from my participants. After analysis and interpretation of data, challenges towards learning mathematics were difficulties in learning mathematics, negative perception and external pressure, disruption in learning environment and foundation, changing teacher and lack of support, enjoyment in mathematics practice and fear of teacher, barriers in conceptual clarity and guidance, obstacles in effective mathematics teaching and disinterest, unclear teaching and insufficient support respectively. Moreover, Students face a multitude of challenges in learning mathematics, including issues related to teacher behavior, lack of motivation, the current curriculum, low parental socio-economic status, ineffective teaching strategies, poor home environments, low academic achievements, math anxiety, impractical curricula, and traditional teaching methods.